Ambulatory blood pressure monitoring in essential hypertensive patients with acute ischaemic stroke - S. P. Zhemanyuk (Zaporožskij Medicinskij Žurnal)
Blood pressure (BP) has been identified as a risk factor for various health disorders, including stroke onsets. Hypertension is one of the crucial health problem among adult Ukrainian. Due to the importance of elevated BP in stroke causality, BP measurement remains critical. However, it is limited information about value in clinical practice of ambulatory blood pressure monitoring (ABPM) data in hypertensive patients with inadequately controlled BP with acute stroke compared with those individuals who has no vascular onset.